Efficacy of Neoadjuvant Chemotherapy DOX and XELOX Regimens for Patients with Resectable Gastric or Gastroesophageal Junction Adenocarcinoma. (23rd July 2021) - Tian, Yuan; Zhao, Qun; Li, Yong; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; Tan, Bibo; Wang, Dong; Yang, Peigang
Abstract : Purpose . This paper is aimed at comparing the short-term efficacy of the combination of docetaxel, oxaliplatin, and capecitabine (DOX) with the combination of oxaliplatin and capecitabine (XELOX) as neoadjuvant chemotherapy regimens for the treatment of patients with resectable gastric or gastroesophageal junction adenocarcinoma. Methods . A total of 300 patients aged 20-60 years with resectable gastric or gastroesophageal junction adenocarcinoma who were evaluated with cT3/4Nany were randomly assigned into 3 groups: DOX group (n = 100, treated with neoadjuvant DOX plus adjuvant XELOX), XELOX group (n = 100, treated with perioperative XELOX), and surgery group (n = 100, treated with adjuvant XELOX). Results . A total of 93, 92, and 95 patients were enrolled in the DOX, XELOX, and surgery groups, respectively. The pathological complete response (pCR) rate was 16.1% in the DOX group and 4.3% in the XELOX group (P = 0.008 ). There were 56 (61.3%) patients in the DOX group who presented with surgical complications, 22 (23.9%) patients in the XELOX group, and 37 (38.9%) patients in the surgery group. The most common grade 3-4 adverse events in these three groups were neutropenia (32.3%, 30.4%, and 21.1%), leucopenia (21.5%, 22.8%, and 15.8%), nausea (15.1%, 16.3%, and 12.6%), and fatigue (10.8%, 7.6%, and 8.4%). Conclusions . Neoadjuvant DOX is an effective and feasible regimen and might represent an option for young and middle-aged patients with locally advanced, resectable gastric or gastroesophageal junction adenocarcinoma.